(untitled) (Research, Society and Development, 2022)
The search for more rationalized and sustainable constructions such as the Light Steel Framing (LSF) system has been increasing worldwide along with the need for a better acoustic performance of the system, in the same way that the demand for research on recycled materials or materials with low environmental impact increases. Thus, the objective of this research is to determine the sound absorption coefficient of a multilayer system formed by recycled-PET fiber and vermiculite board, to be used inside the walls of the LSF constructive system, through acoustic impedance tubes, according to ASTM E 1050 (2019). The tests were performed on 60 mm diameter samples of recycled-PET fiber and vermiculite board individually and samples with two layers, one of the combinations was with the vermiculite board in the innermost part of the tube and the recycled-PET fiber just ahead and the other way, inverting their positions. The results showed that the best performance for sound absorption for frequencies above 1000 Hz was the two-layer system, with vermiculite in the innermost part of the tube and recycled-PET fiber in the outermost part. The lowest performance was the recycled-PET fiber used in isolation, it did not present values greater than 0,5 in the entire frequency range analyzed. Therefore, it was possible to conclude that the use of the vermiculite board together with the recycled-PET fiber is an absorber system capable of optimizing the acoustic performance of the LSF system.